Nature and urban space occupation. the city parks (2010)
This paper studies the public and private urban space, and the necessity of the inhabitants to create iconic symbols to allow the configuration of urban proud and social identity. Our conceptual analysis has been applied to examples of urban intervention –to the parks particularly- that have change their surroundings. The environment preservation and the creation of the infrastructure have motivated the renewal of low rent home areas, urban and market value and have modified the urban proud and identity of inhabitants and travelers of the private and public spaces.